2009
DOI: 10.1016/j.ydbio.2009.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Diverging functions of Scr between embryonic and post-embryonic development in a hemimetabolous insect, Oncopeltus fasciatus

Abstract: Hemimetabolous insects undergo an ancestral mode of development in which embryos hatch into first nymphs that resemble miniature adults. While recent studies have shown that homeotic (hox) genes establish segmental identity of first nymphs during embryogenesis, no information exists on the function of these genes during post-embryogenesis. To determine whether and to what degree hox genes influence the formation of adult morphologies, we performed a functional analysis of Sex combs reduced (Scr) during post-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 39 publications
10
76
0
Order By: Relevance
“…Injections and dsRNA synthesis were performed as previously described (16). Detailed information including primer sequences and RT-PCR controls, are in SI Material and Methods and Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Injections and dsRNA synthesis were performed as previously described (16). Detailed information including primer sequences and RT-PCR controls, are in SI Material and Methods and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Depletion via RNAi of the homeotic gene Sex combs reduced (Scr), which regulates T1 segmental identity (8), results in the formation of a small ectopic wing on T1 (16). Similar small T1 wings are present in diverse early insect fossils (2).…”
Section: Insights About Wing Origins and Functionalization From T1 Ecmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent gene functional analyses of beetles (Coleoptera) and the milkweed bug (Hemiptera) demonstrated that serially homologous structures of wings in thoracic and abdominal segments are promoted or inhibited to differentiate into wings depending on the regulation of Hox genes and the wing gene network [10][11][12][13][14]. This scenario might be applied to basal winged species, the mayfly Ephoron eophilum (Ephemeroptera) and even to non-winged species, the bristletails Pedetontus unimaculatus (Apterygota, Archaeognatha) [15].…”
Section: Introduction: Morphological Diversities Of Insects' Wing Venmentioning
confidence: 99%